Indeginisation of democracy: harnessing traditional leadership in promoting democratic values in Zimbabwe - Chakunda, Vincent; Chikerema, Arthur (American Research Institute for Policy Development, 2020)
The juxtaposition of traditional leadership against democratic governance has been one of the most disputed and contested areas in social sciences. The debate has triggered many theories, criticisms and counter criticisms over the permeability and porosity of traditional systems of authority to embrace democratic principles in their operations. Two main streams of contesting arguments have discerned from modernists on the one hand and traditionalists on the other hand. Modernists have to a large extent disregarded traditional governance systems and structures as atavistic and pedantic and as such not only a direct contrary of democracy but the antithesis and nemesis of the latter. They (modernists) view traditional authority as a gerontocratic, chauvinistic, authoritarian and increasingly irrelevant form of rule that is antithetical to democracy. As such modernists perceive traditional political systems as relics of the past that may actually impede democratic development, and which must therefore be overcome (Logan Caroln1 . Modernists have sceptically labelled traditional leadership systems as a major setback to democracy holding traditional values which are patriarchal, silencing the views of youth and women and have condemned traditional leaders as the least qualified to talk about democracy. On the contrary, traditionalists regard Africa’s traditional chiefs and elders as the true representatives of their people, accessible, respected, and legitimate, and therefore still essential to politics on the continent. But the question that remains sticking, which is also the central discourse to be resolved by this paper is, are traditional leaders the anti-thesis of democracy? This paper was motivated by Kwesi Kwaa Prah’s Democracy, Education, Literacy and Development (Keynote Address; 10th Year Jubilee Celebrations of the Centre for International Education, University College of Oslo, 28th – 30th August, 20072 .) where he submitted that, “democracy is best indigenized. It succeeds best when it wears and acknowledges the specific historical and cultural realities of the society in question”. While the focus of Prah’s paper was on the linkages of democracy, education, literacy and development as key variables given, this paper dissects how the institution of traditional leadership in Zimbabwe can be harnessed to promote democratic governance in the country. While the view is widely held that Africa's democratization should draw from its cultural traditions, little has been done to analyze systematically the extent to which this does or can occur Donald